Observational properties of ultra-diffuse galaxies in low-density environments: field UDGs are predominantly blue and star forming. Issue 2 (5th July 2019) - Prole, D J; van der Burg, R F J; Hilker, M; Davies, J I
Abstract: While we have learnt much about ultradiffuse galaxies (UDGs) in groups and clusters, relatively little is known about them in less dense environments. More isolated UDGs are important for our understanding of UDG formation scenarios because they form via secular mechanisms, allowing us to determine the relative importance of environmentally driven formation in groups and clusters. We have used the public Kilo-Degree Survey together with the Hyper Suprime-Cam Subaru Strategic Program to constrain the abundance and properties of UDGs in the field, targeting sources with low surface brightness (24.0 ≤ $\bar{μ }_{ e, r}$ ≤ 26.5) and large apparent sizes (3.0 arcsec ≤ $\bar{r}_{ e, r}$ ≤ 8.0 arcsec). Accounting for several sources of interlopers in our selection based on canonical scaling relations, and using an empirical UDG model based on measurements from the literature, we show that a scenario in which cluster-like red-sequence UDGs occupy a significant number of field galaxies is unlikely, with most field UDGs being significantly bluer and showing signs of localized star formation. An immediate conclusion is that UDGs are much more efficiently quenched in high-density environments. We estimate an upper limit on the total field abundance of UDGs of 8 ± 3 × 10 −3 cMpc −3 within our selection range. We also compare the total field abundance of UDGs to a measurement of the abundance of H i -rich UDGs from the literature, suggesting that they occupy at least one-fifth of the overall UDG population. The mass formation efficiency of UDGs implied by this upper limit is similar to what is measured in groups and clusters.